Acyl-CoA synthetase activity in liver microsomes from calcium-deficient rats - Marra, Carlos Alberto (1999)
A study on the kinetic properties of the nonspecific acyl-coenzyme A (CoA) synthetase activity in liver microsomal vesicles from both normal and calcium-deficient Wistar rats was carried out. After a 65-d treatment, the calcium-deficient diet reflected a 75% increase in the synthetase activity with respect to control animals. The apparent Vm was significantly enhanced, while the Km remained unchanged. We also provided experimental evidence about various fatty acids of different carbon length and unsaturation which depressed the biosynthesis of palmitoyl-CoA following different behaviors in control or calcium-deprived liver microsomes. In addition, we studied in detail the inhibition reflected by stearic, α-linolenic, or arachidonic acids, in the biosynthesis of palmitoyl-CoA in microsomal suspensions either from control or hypocalcemic rats. In control microsomes, stearic acid produced a pure competitive effect, while the other fatty acids followed a mixed-type inhibition. The competitive effect of stearic acid was not observed in calcium-deprived microsomes. At the same time, a mixed-type inhibition produced by either α-linolenic or arachidonic acid was diminished in deprived microsomes due to an increase in the noncompetitive component (αKi). These changes observed in apparent kinetic constants (Km, Vm, Ki, and αKi), as determined by Lineweaver-Burks and Dixon plots, were attributed to the important alterations in the physicochemical properties of the endoplasmic reticulum membranes induced by the calcium-deficient diet. The solubilization of the enzyme activity from both types of microsomes demonstrated that the kinetic behavior of the enzyme depends on the microenvironment in the membrane, and that the calcium ion plays a crucial role in determining the alterations observed.